2011
DOI: 10.1037/a0022334
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being in retirement: The effects of personal and gendered contextual resources.

Abstract: Although prior research points to the gendered nature of work and private routines, surprisingly few studies have explored the influence of gender on the sources of psychological well-being in retirement. Drawing on resource theories and theories on the gendered division of labor, this study examines how preretirement resources relate to retirees’ psychological well-being by using data from the Wisconsin Longitudinal Study. It is hypothesized that possessing key resources prior to retirement as well as losing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 72 publications
4
58
0
1
Order By: Relevance
“…The first is related to the study's focus on only two cities in Minas Gerais State, making it impossible to generalize the results to the whole country of Brazil. The second limitation is that happiness of retirees could be related to other personal issues, such as optimism, resiliency, and personal characteristics that were not tested, according to Lyubomirsky (2001) and Kubicek, et al (2011). These limitations led to recommendations for future studies involving these personal qualities, especially longitudinal studies, which are rare in the Brazilian context and can explain how the changes on the main retirement resources, personal characteristics, or status can influence the well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is related to the study's focus on only two cities in Minas Gerais State, making it impossible to generalize the results to the whole country of Brazil. The second limitation is that happiness of retirees could be related to other personal issues, such as optimism, resiliency, and personal characteristics that were not tested, according to Lyubomirsky (2001) and Kubicek, et al (2011). These limitations led to recommendations for future studies involving these personal qualities, especially longitudinal studies, which are rare in the Brazilian context and can explain how the changes on the main retirement resources, personal characteristics, or status can influence the well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The factors relevant for planning retirement are (i) long-term risk factors, such as health promotion (Kubicek et al 2011;Van Solinge and Henkens 2008), financial aspects (Hershey et al 2010), and individual and collective quality of life (França 2004;Peiró et al 2013); (ii) medium-and shortterm factors of well-being, such as intellectual development and diverse activities (social and leisure activity, hobbies, cultural and physical activities, volunteer opportunities, and routine tasks) (Nimrod and Shrira 2014;Oerlemans et al 2011); and (iii) life-long learning (França 2012), seeking social support (Wang and Schultz 2010), and work, social, affective, and family bonds (Antonucci 2001). Brazilian studies on key aspects of retirement planning have found that for both executives (França 2004) and non-management workers, the most important factor in life is health, especially aspects related to nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study conducted by Kubicek and her collaborators, two personal resources predicted higher levels of well-being in retirement (Kubicek et al, 2011), namely, retirees' perseverance in pursuing their goals, and retirees' flexibility in adjusting their goals. Given that retirement involves inevitable gains (e.g., more time and freedom) and losses (e.g., reduced income, loss of "worker" identity), these two personal resources promote the maintenance of A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, a person's financial and physical resources (wealth and health) are associated with retirement intentions such that those who suffer poor health intend to retire earlier as do those who can financially afford to do so. Health and wealth are also related to mental health post-retirement (Kubicek, Korunka, Raymo, & Hoonakker, 2011). A person's education, which can be considered a cognitive resource, has also been associated with later retirement intentions (Damman, Henkens, & Kalmijn, 2011;Szinovacz, Davey, & Martin, 2015).…”
Section: Personal Factors: Personality and Resourcesmentioning
confidence: 99%